EXPRESS DIAGNOSTICS OF ORAL FLUID FOR THE PRESENCE OF VOLATILE AMINES IN WOMEN WITH BACTERIAL VAGINOSIS - Shulzhenko, A.; Krutikova, E.; Petrushanko, T.; Ostrovska, L. (World of Medicine and Biology, 2018)
72 women of the age of 18-45 years were studied, who studied the dental and gynecological statuses. BV was diagnosed by obstetrician-gynecologists. Clinical diagnosis of the condition of the oral cavity of the examined was carried out. The presence of Gardnerella vaginalis and Atopobium vaginae was determined by the PCR method in the oral cavity and vagina. An amine oral fluid test with BV has been developed and patented. All patients with BV are diagnosed with inflammatory and inflammatory-dystrophic periodontal diseases. Indicators of oral amine oral test are positive in 100% of patients with BV. Amino-test should be considered an effective method of rapid diagnosis of the presence in the oral cavity of pathogens of bacterial vaginosis.